AKTIVITAS ANTIMITOSIS EKSTRAK ETANOL 80% LAWI-LAWI (Caulerpa racemosa) TERHADAP SEL ZIGOT BULU BABI (Tripneustes gratilla) - Feriadi, Eva; Al Awaldhi Ramadhan; Muh. Syahruddin; Febrianto Patulak; Diah Fausiah (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Cancer remains one of the leading causes of mortality worldwide, characterized by a high prevalence rate and ranking as the second most common cause of death globally. The elevated prevalence of cancer is closely associated with its hallmark features of uncontrolled cellular proliferation and aberrant mitotic processes. One plant species proposed to possess antimitotic potential is the lawi-lawi plant (Caulerpa racemosa). The bioactive compounds contained within this alga have been demonstrated to exhibit diverse pharmacological activities and are traditionally utilized by Indonesian communities as a natural source of antioxidants. This study employed a quantitative approach using a true experimental post-test-only control group design to evaluate the effect of an 80% ethanol extract of C. racemosa on the inhibition of mitosis in sea urchin (Tripneustes gratilla) zygote cells. The results of the antimitotic assay revealed that the C. racemosa extract exhibited an IC₅₀ value of 208.93 µg/mL, whereas the positive control, Vincristine, demonstrated a markedly lower IC₅₀ value of 2.46 µg/mL. These findings indicate that the 80% ethanol extract of C. racemosa possesses measurable antimitotic activity, although its potency is moderate when compared with the strong inhibitory effect exhibited by Vincristine.